2021
DOI: 10.1002/jbm.b.34834
|View full text |Cite
|
Sign up to set email alerts
|

Zinc‐ and strontium‐ co‐incorporated nanorods on titanium surfaces with favorable material property, osteogenesis, and enhanced antibacterial activity

Abstract: Early infection and peri‐implantitis after implant restoration are major reasons for dental implant failure. Implant‐associated infections are majorly attributed to biofilm formation. In this study, co‐incorporated zinc‐ (Zn‐) and strontium‐ (Sr‐) nanorod coating on sandblasted and acid‐etched (SLA) titanium (SLA‐Zn/Sr) was fabricated by hydrothermal synthesis. It was aimed at promoting osteogenesis while inhibiting biofilm formation. The nanorod‐like particles (φ 30–50 nm) were found to be evenly formed on SL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 75 publications
0
11
0
Order By: Relevance
“…In the current study, the Sr 2+ release levels are less than 9.5 ppm at day 1 and 0.03 ppm at day 30, which are far below the concentration mentioned above to exert a negative effect. It is interesting to see that most of studies on Ti coatings, including Sr/Zn‐containing TiO 2 coating, 4 TiCPCF‐Sr coating, 19 Sr/Ag‐containing TiO 2 coating, 10 SLA‐Zn/Sr nano‐rod coating, 24 Sr 2+ release were also controlled at similar levels ranging from 0.479 to 6.0 ppm. In another study by Barrioni et al, the effective Sr 2+ concentrations on osteogenesis of Sr‐containing bioceramics ranged from 2 to 6 μg/mL (2–6 ppm), 23 which are compatible to our results.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the current study, the Sr 2+ release levels are less than 9.5 ppm at day 1 and 0.03 ppm at day 30, which are far below the concentration mentioned above to exert a negative effect. It is interesting to see that most of studies on Ti coatings, including Sr/Zn‐containing TiO 2 coating, 4 TiCPCF‐Sr coating, 19 Sr/Ag‐containing TiO 2 coating, 10 SLA‐Zn/Sr nano‐rod coating, 24 Sr 2+ release were also controlled at similar levels ranging from 0.479 to 6.0 ppm. In another study by Barrioni et al, the effective Sr 2+ concentrations on osteogenesis of Sr‐containing bioceramics ranged from 2 to 6 μg/mL (2–6 ppm), 23 which are compatible to our results.…”
Section: Discussionmentioning
confidence: 99%
“…Low concentration of Sr benefit adhesion, proliferation and osteogenic differentiation of bone mesenchymal stem cells (BMSCs) and preosteoblats, as well as angiogenic activity of human umbilical vein endothelial cells (HUVECs) 3–8,10,18–23 . Nevertheless, higher Sr concentration has deleterious effect on these biological processes 4,19–21,24 . This is also supported by in vivo investigations, in which low dose Sr can improve bone microarchitecture to prevent or treat osteoporosis, 25,26 whereas high dose and long‐term use may lead to some cardiovascular side effects 27 .…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Recently, strontium (Sr) has been clinically used to treat osteoporosis through activating the calcium‐sensing receptor in osteoclasts or osteoblasts, which further modulates MAPK ERK1/2 and Wnt/NFATc signaling pathways to promote osteogenesis 13 . Our previous studies have confirmed that Sr‐incorporated titanium implants and Zn/Sr‐co‐incorporated titanium implants did well in promoting rapid bone formation 14–17 . However, the potential mechanisms remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The work-flow of the present study titanium implants and Zn/Sr-co-incorporated titanium implants did well in promoting rapid bone formation. [14][15][16][17] However, the potential mechanisms remain unclear.…”
Section: Introductionmentioning
confidence: 99%